Patterns of Genomic Divergence Across Geographically Variable Populations of Cerasus campanulata (Maxim.) Yu et Li (Rosaceae) - Xiuming Xu; Hongyao Hu; Enwen Lin; Lumei Liu; Yuchong Yi; Yingjia Shen; Xiaokai Ma; Shipin Chen (Plant Molecular Biology Reporter, 2026)

The use of the serum progesterone strip test as a clinical tool for assessing reproductive status in replacement gilts - Preechaphon Taechamaeteekul; Umaporn Pimpitak; Junpen Suwimonteerabutr; Wanwisa Poonlapdecha; Nutthiwut Khun-arwut; Kittinan Komolpis; Sirirat Rengpipat; Kridtasak Sang-Gassanee; Hongyao Lin; Miquel Collell; Robert V. Knox; Padet Tummaruk (Theriogenology, 2025)

Effects of Angelica sinensis polysaccharides on growth performance, antioxidant capacity, immune response, intestinal microbiota, and liver transcriptome in Mauremys mutica - Zike Yan; Jingu Shi; Kaijie Lin; Yuhan Li; Yutian Zhan; Mingzuo Gao; Hongyao Zhang; Shuyu Han; Jingzhen Liang (Aquaculture International, 2025)

Supplementation of boar semen extender with 5 μg of buserelin improves litter size and birth weight in gilts raised under tropical field conditions - Preechaphon Taechamaeteekul; Yosua Kristian Adi; Junpen Suwimonteerabutr; Kridtasak Sang-Gassanee; Hongyao Lin; Miquel Collell; Robert V. Knox; Padet Tummaruk (Theriogenology, 2025)

Gene Interaction of Dopaminergic Synaptic Pathway Genes in Attention-Deficit Hyperactivity Disorder: a Case-Control Study in Chinese Children - Lin Zhong; Hongyao He; Jing Zhang; Xiaoyan Gao; Feifei Yin; Pengxiang Zuo; Ranran Song (Molecular Neurobiology, 2024)
Attention-deficit hyperactivity disorder is a highly inherited neurodevelopmental disorder. Previous genetic research has linked ADHD to certain genes in the dopaminergic synaptic pathway. Nonetheless, research on this relationship has produced varying results across various populations. China is a multi-ethnic country with its own unique genetic characteristics. Therefore, such a population can provide useful information about the relationship between gene polymorphisms in dopaminergic synaptic pathways and ADHD. This study looked at the genetic profiles of 284 children in China’s Xinjiang. In total, 142 ADHD children and 142 control subjects were enrolled. Following the extraction of DNA from oral mucosal cells, 13 SNPs for three candidate genes (SLC6A3, DRD2, and GRIN2B) in the dopaminergic synaptic pathway of ADHD were screened. Based on the results of single nucleotide polymorphism (SNP) analyses, we found that the DRD2 gene variants rs6277 and rs6275, and the SLC6A3 gene variant rs2652511, were significantly associated with ADHD in boys and girls, respectively, after adjusting for false discovery rate (FDR) in terms of allele frequencies. Furthermore, our generalized multifactorial downscaling approach identified a significant association between rs6275 and rs1012586. These findings suggest that DRD2 and SLC6A3 genes have a crucial role in ADHD susceptibility. Additionally, we observed that the interaction between GRIN2B and DRD2 genes may contribute to the susceptibility of Chinese children with ADHD.